2021
DOI: 10.1126/scitranslmed.aaz4957
|View full text |Cite
|
Sign up to set email alerts
|

4-Aminopyridine is a promising treatment option for patients with gain-of-function KCNA2 -encephalopathy

Abstract: 4-Aminopyridine is a potential therapeutic option for a subgroup of patients with KCNA2 -encephalopathy and gain-of-function variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 66 publications
0
47
0
1
Order By: Relevance
“…Studies on diagnosis and recovery from peripheral nerve injury have already led to two clinical trials on 4-AP treatment of acute injuries [ 28 , 29 ]. A recent report of 4-AP treatment in patients with KCNA2-encephalopathy has interesting mechanistic implications; 4-AP reduced seizures in patients with gain-of-function variants of the Kv1.2 subunit and antagonized the electrophysiological defects in vitro in transfected neurons that expressed variant Kv1.2 channels [ 37 ]. In addition, methods to evaluate 4-AP target engagement and potential mechanism(s) of action in the brain may be facilitated by development of a 4-AP radioligand for neuroimaging, which has detected cortical pathology from brain injury in nonhuman primate testing and has advanced to a clinical trial [ 9 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on diagnosis and recovery from peripheral nerve injury have already led to two clinical trials on 4-AP treatment of acute injuries [ 28 , 29 ]. A recent report of 4-AP treatment in patients with KCNA2-encephalopathy has interesting mechanistic implications; 4-AP reduced seizures in patients with gain-of-function variants of the Kv1.2 subunit and antagonized the electrophysiological defects in vitro in transfected neurons that expressed variant Kv1.2 channels [ 37 ]. In addition, methods to evaluate 4-AP target engagement and potential mechanism(s) of action in the brain may be facilitated by development of a 4-AP radioligand for neuroimaging, which has detected cortical pathology from brain injury in nonhuman primate testing and has advanced to a clinical trial [ 9 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a second step, emerging aimed therapeutic considerations are starting to be delineated for a number of DEE entities, relating to the optimization of indications of known anti-seizure drugs, and repurposing of drugs without epilepsy-related indications. Examples of these strategies are the possible favorable response to specific antiseizure medications (KCNQ2 DEE and sodium channel blockers), other families of drugs (KCNA2 DEE with gain of function and aminopyridine) or dietary treatments (SLC2A1 and ketogenic diet), the avoidance of specifically harmful drugs in some entities (POLG encephalopathies and valproic acid) (6,(81)(82)(83), or the possible tendency to relapse manifested by patients with other DEEs when discontinuing anti-seizure medication after a long seizure-free period (PCDH19 DEE), among many other examples (84,85).…”
Section: Clinical Implications Of Diagnosis: Optimization Of Therapy ...mentioning
confidence: 99%
“…4-aminopyridine is a potassium channel blocker that can antagonize GOF defects in the KCNA2 gene that cause a DEE. In a study of n-of-1 trials in nine different centers, nine of 11 patients showed improvement in seizure burden, gait, ataxia, alertness, and cognition after starting 4-aminopyridine ( 43 ). Because of these findings, it seems a promising tailored treatment for KCNA2-encephalopathy caused by GOF variants.…”
Section: Therapies For Genetic Epilepsiesmentioning
confidence: 99%